2008
DOI: 10.1002/cta.563
|View full text |Cite
|
Sign up to set email alerts
|

Explicit design formulas for current‐mode leap‐frog OTA‐C filters and 300 MHz CMOS seventh‐order linear phase filter

Abstract: SUMMARYThe leap-frog (LF) configuration is an important structure in analogue filter design. Voltage-mode LF OTA-C filters have recently been studied in the literature; however, general explicit formulas do not exist for current-mode LF OTA-C filters and there is also need for current-mode LF-based OTA-C structures for realization of arbitrary transmission zeros. Three current-mode OTA-C structures are presented, including the basic LF structure and LF filters with an input distributor or an output summer. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In particular, general nth-order inverse-follow-the leader-feedback (IFLF) [1,2] and leap-frog (LF) feedback OTA-C configurations have been derived. More recently, explicit design formulas for LF OTA-C filters have also been derived [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, general nth-order inverse-follow-the leader-feedback (IFLF) [1,2] and leap-frog (LF) feedback OTA-C configurations have been derived. More recently, explicit design formulas for LF OTA-C filters have also been derived [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Applications such as high-frequency continuoustime (CT) analog OTA-C filters provide solutions for various signal processing tasks [1][2][3][4][5][6][7][8][9][10][11]. In the recent years, also the field programmable analog arrays based on the tunable (programmable) OTAs 886 S. SZCZEPANSKI, B. PANKIEWICZ AND S. KOZIEL and integrating capacitors (C) have been developed successfully to built reconfigurable hardware platforms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Given a transfer function and desired specifications, different filter topologies may be suitable. It has been demonstrated that MLF Gm-C filter structures can realise transfer functions with arbitrary zeros [4,5], a feature that is particularly useful for wavelet filters since wavelet approximations often result in non-traditional zeros. MLF structures also have lower magnitude sensitivity than cascade topologies and use only grounded capacitors.…”
mentioning
confidence: 99%
“…First of all, two transconductors are required in the LFF structure for realising the transmission zeros of (1), while only one transconductor is needed in the FLF structure. Also, to produce the only term in the numerator, the two transconductors in the LFF circuit need exact matching (equal values) to null an additional unwanted constant from the circuit [5]. Difference nulling is very sensitive to transistor mismatches in high frequency, which should thus be avoided in practical IC design.…”
mentioning
confidence: 99%
See 1 more Smart Citation